Acute complications of jejunal-ileal lymphoma - González, Daniel; Ruso, Luis; Rodríguez, Gustavo; Plazzotta, Cecilia; Rondán, Mariela; di Leoni, Francisco; Balboa, Oscar (Cirugía del Uruguay, 2004)
Sma/1 íntestine lymphoma is a entíty whose íncídence fluctuates between 1 and 4% of ali malignant tumors of digestíve tract. lts usual clínica/ presentatíon is in the form of acute abdominal symptomatology thus determíníng that the surgeon general/y comes across them in urgency servíces. The surgícal treatment is estab/ished under these círcumstances, oftentímes /ackíng and establíshed etíologíc diagnosis, Anatomo-pathologic confírmatíon renders possíble settíng up adjuvant treatment on the basis of chemo and radío therapy